Orquestra de violões da Paraíba: perspectivas sobre a formação docente - Sousa, Johnatan Martins de (2022)
In recent years, studies on teaching guitar in group have grown significantly in the literature of music education. This teaching method has been used in the initial training of guitarists, but some teachers also explore this proposal in the higher education context. From this scenario, there is a need to study the education of teachers who work in this context, and this paper focuses on the education of music teachers who work with teaching guitar in group. The central objective here is to understand how guitar practice and teaching praxis relate to the training of monitors in the Paraíba Guitar Orchestra project. For this, a qualitative approach research was developed, with fieldwork conducted from February to December 2021. The fieldwork was based on the observation in the context of the Orquestra de violões da Paraíba (Paraíba Guitar Orchestra), as well as the application of semi-structured interviews with the coordination and four monitors who work in guitar practice and in the guitar class in group. The work was based on studies from the field of music education, more specifically on perspectives about the training of the musician-teacher and about cooperative and collaborative musical learning. The results of the research indicate that the monitors have characteristics in common, since they start from a practical perspective. But, at the same time, they have different methodological conducts according to their affinities and teaching vision. It was possible to verify that the monitors see the two fronts of the project as complementary to each other. Thus, the difficulties and knowledge experienced in the guitar class in group were also experienced in the guitar practice. The strategies for conducting were also in tune, and musical arrangements emerged as a means of teaching-learning on both fronts. Guitar practice and teaching praxis were related from the practical conduct to the specific conductions of each monitor, as each adopted and experimented methodology emerged from a collaborative collective construction among the group.